Acute‐onset smell and taste disorders in the context of COVID‐19: a pilot multicentre polymerase chain reaction based case–control study - Beltrán‐Corbellini, Á.; Chico‐García, J. L.; Martínez‐Poles, J.; Rodríguez‐Jorge, F.; Natera‐Villalba, E.; Gómez‐Corral, J.; Gómez‐López, A.; Monreal, E.; Parra‐Díaz, P.; Cortés‐Cuevas, J. L.; Galán, J. C.; Fragola‐Arnau, C.; et al. (European journal of neurology, 2020)
Background and purpose Specific respiratory tract infections, including COVID‐19, may cause smell and/or taste disorders (STDs) with increased frequency. The aim was to determine whether new‐onset STDs are more frequent amongst COVID‐19 patients than influenza patients. Method This was a case–control study including hospitalized patients of two tertiary care centres. Consecutive patients positive for COVID‐19 polymerase chain reaction (cases) and patients positive for influenza polymerase chain reaction (historical control sample) were assessed during specific periods, employing a self‐reported STD questionnaire. Results Seventy‐nine cases and 40 controls were included. No significant differences were found in basal features between the two groups. New‐onset STDs were significantly more frequent amongst cases (31, 39.2%) than in the control group (5, 12.5 %) [adjusted odds ratio 21.4 (2.77–165.4, P = 0.003)]. COVID‐19 patients with new‐onset STDs were significantly younger than COVID‐19 patients without STDs (52.6 ± 17.2 vs. 67.4 ± 15.1, P < 0.001). Amongst COVID‐19 patients who presented STDs, 22 (70.9%) recalled an acute onset and it was an initial manifestation in 11 (35.5%). Twenty‐five (80.6%) presented smell disorders (mostly anosmia, 14, 45.2%) and 28 (90.3%) taste disorders (mostly ageusia, 14, 45.2%). Only four (12.9 %) reported concomitant nasal obstruction. The mean duration of STD was 7.5 ± 3.2 days and 12 patients (40%) manifested complete recovery after 7.4 ± 2.3 days of onset. Conclusion New‐onset STDs were significantly more frequent amongst COVID‐19 patients than influenza patients; they usually had an acute onset and were commonly an initial manifestation. The use of STD assessment in anamnesis as a hint for COVID‐19 and to support individuals’ self‐isolation in the current epidemic context is suggested.